2017
DOI: 10.1037/xan0000109
|View full text |Cite
|
Sign up to set email alerts
|

Serial pattern learning in pigeons: Rule-based or associative?

Abstract: Extensive research has documented evidence for rule learning in sequential behavior tasks in both rats and humans. We adapted the 2-choice serial multiple choice (SMC) task developed for use with rats (Fountain & Rowan, 1995a) to study sequence behavior in pigeons. Pigeons were presented with 8 disks arranged in a circular array on a touchscreen, and pecking to an illuminated disk could lead to reward. Correct responding consisted of serial patterns involving ‘run’ chunks of three elements (123 234, etc.). Som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 60 publications
1
16
0
Order By: Relevance
“…In essence, it has frequently been noted that hierarchical patterns are characterized by a fundamental ambiguity in that they can potentially be represented in multiple ways (Fountain, ; Fountain & Doyle, ; Greeno & Simon, ; Jones, ). This issue has been most elegantly addressed by Fountain and colleagues (Fountain, ; Fountain & Doyle, ; Fountain & Rowan, ; Garlick et al, ; Muller & Fountain, ) who have provided compelling evidence for the existence of hierarchical versus associative representations in animals. For our purposes, the critical aspect is not the exact nature of the hierarchical representation, but rather that our findings demonstrate that infants can reliably discriminate hierarchically structured from non‐hierarchically (e.g., linear or associative) patterns.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In essence, it has frequently been noted that hierarchical patterns are characterized by a fundamental ambiguity in that they can potentially be represented in multiple ways (Fountain, ; Fountain & Doyle, ; Greeno & Simon, ; Jones, ). This issue has been most elegantly addressed by Fountain and colleagues (Fountain, ; Fountain & Doyle, ; Fountain & Rowan, ; Garlick et al, ; Muller & Fountain, ) who have provided compelling evidence for the existence of hierarchical versus associative representations in animals. For our purposes, the critical aspect is not the exact nature of the hierarchical representation, but rather that our findings demonstrate that infants can reliably discriminate hierarchically structured from non‐hierarchically (e.g., linear or associative) patterns.…”
Section: Discussionmentioning
confidence: 99%
“…In essence, it has frequently been noted that hierarchical patterns are characterized by a fundamental ambiguity in that they can potentially be represented in multiple ways (Fountain, 2008;Fountain & Doyle, 2011;Greeno & Simon, 1974;Jones, 1981). This issue has been most elegantly addressed by Fountain and colleagues (Fountain, 2008;Fountain & Doyle, 2011;Fountain & Rowan, 1995;Garlick et al, 2017;Muller & Fountain, 2016) who have provided compelling evidence for the existence of hierarchical versus associative representations in animals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior studies have shown that pigeons will naturally (i.e., without explicit reinforcement) encode sequences of locations (Froehlich et al, 2004;Herbranson & Stanton, 2011;Herbranson, Xi, & Trinh, 2014), though they can also learn sequences through reinforcement (Garlick, Fountain, & Blaisdell, 2016). Perhaps prior studies that failed to show lasting feature binding resulted from procedures that failed to sufficiently increase the salience of, and thereby attention to feature conjunctions.…”
Section: Binding In Pigeons 15mentioning
confidence: 99%